FAKTOR-FAKTOR YANG MEMPENGARUHI PERBEDAAN BERAT BADAN LAHIR BAYI DI RSUD. Dr. M . YUNUS KOTA BENGKULU - Marisiantini, Meli (JURNAL MEDIA KESEHATAN, 2015)
Nowadays, Infant Mortality Rate (IMR) is still high in Indonesia, it is about 32 per 1.000 livebirths, and low birth weight infants accounted for 34% as the major cause (SDKI, 2012). InDr.M.Yunus hospital at Bengkulu city, cases of LBW has increased from the preceding year,approximately 391 infants (14.4%) of 2713 childbirths. The purpose of this research is known thefactors which affect average of birth weight infants in C1 Midwifery room at Dr.M.Yunus Bengkulu in2013. The study design was observational descriptive with cross-sectional method which the populationare women who delivered in the maternity room at Dr.M.Yunus hospital, and also with accidentalsampling technique which samples are 48 respondents, data were processed using univariate andbivariate. The results of statistical tests showed there are influences of those factors to affect average ofbirth weight infant in Dr.M.Yunus hospital in 2013 and long-standing is the most dominant factor. It isexpected that health workers can be provide counseling to pregnant women in order to know the risks ifthe women have a bad lifestyle (exposure to cigarette smoke, caffeine consumption, and prolongedstanding) and also set the age for pregnancy planning.